Parent Involvement in School Conceptualizing Multiple Dimensions and Their Relations with Family and Demographic Risk Factors - Kohl, Gwynne O. (2000)
Parent involvement (PI) in school is associated with more positive academic performance and social competence in children. However, there are inadequacies in current measures of PI and a need for a better understanding of predictors of PI. In this study, measures were obtained from a normative sample of 387 children in kindergarten and first grade from high-risk neighborhoods in 4 different sites. First, a confirmatory factor analysis of a theoretical factor model of PI identified 6 reliable multiple-reporter PI factors: Parent—Teacher Contact, Parent Involvement at School, Quality of Parent—Teacher Relationship, Teacher’s Perception of the Parent, Parent Involvement at Home, and Parent Endorsement of School. Next, the relations among 3 specific family and demographic risk factors—parental education level, maternal depression, and single-parent status—and these 6 PI factors were examined using path analyses in structural equation modeling. Results indicated that the 3 risk factors were differentially associated with the 6 PI factors: Parental education was significantly associated with 4 PI outcomes, maternal depression was significantly associated with 5 PI outcomes, and single-parent status was significantly associated with 3 PI outcomes. No significant ethnic group differences between African American and Caucasian families were found in these relations.